Effect of washing and torrefaction pretreatments on fuel properties of rice husk-based bio-pellets - Alchalil Alchalil; Rizky Iskandar; Adi Setiawan; Zulmiardi Zulmiardi; Athiyah Rana; Azhar Syahputra (Politeknik Negeri Lhokseumawe, 2026)
Rice husk is an abundant agricultural waste in Indonesia and has potential as a biomass fuel for co-firing in steam power plant boilers. This study investigated the effects of washing and torrefaction pretreatments on the fuel properties of rice husk-based bio-pellets to reduce ash content and improve calorific value. Rice husk was washed using water at 70 ± 5°C under two conditions, with stirring and without stirring, while untreated rice husk was used as a control. Torrefaction was conducted at 260°C, and the treated biomass was pelletized using tapioca starch as a binder at 30% of the raw material weight. The results showed that the lowest ash content (26.362%) was obtained from bio-pellets produced from rice husk washed without stirring, indicating that washing was effective in reducing ash content. The highest calorific value (4456.4 kcal/kg) was recorded in bio-pellets produced from untreated rice husk, while the highest combustion rate (0.504 g/min) was observed in the washed and torrefied samples. The findings indicate a trade-off between ash reduction and energy performance, depending on the pretreatment combination. However, all samples showed relatively high ash content (26%–36%), which may limit their direct suitability for co-firing without further ash reduction treatment.